1993
DOI: 10.1099/0022-1317-74-7-1227
|View full text |Cite
|
Sign up to set email alerts
|

Close similarity between genome structures of rice black-streaked dwarf and maize rough dwarf viruses

Abstract: The complete nucleotide sequences of rice blackstreaked dwarf virus (RBSDV) genome segments 8 ($8) and 7 ($7) were determined, and were found to have high sequence identities to the corresponding maize rough dwarf virus (MRDV) genome segments. RBSDV $8 and $7 consisted of 1927 and 2193 nucleotides, respectively. RBSDV $8 had a single long open reading frame (ORF)encoding 591 amino acids. RBSDV $7 had two nonoverlapping ORFs encoding 362 (ORF1) and 309 (ORF2) amino acids. The two ORFs of RBSDV $7 were inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…et al, 1991) ; a similar dicistronic structure has been found in RBSDV S7 (Azuhata et al, 1993) and MRDV S8 (Marzachı! et al, 1996).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…et al, 1991) ; a similar dicistronic structure has been found in RBSDV S7 (Azuhata et al, 1993) and MRDV S8 (Marzachı! et al, 1996).…”
Section: Introductionsupporting
confidence: 59%
“…cDNA clones were generated from either viral transcripts (Azuhata et al, 1993) or genomic dsRNA (Uyeda et al, 1990) and those from S9 were selected by hybridization using S9 as a probe. One clone that covered about 80 % of S9 from the 3h end and four clones that covered the 5h-terminal region were used for sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azuhata et al, 1992). However, RBSDV and MRDV belong to the same Fijivirus group and are believed to be closely related (Azuhata et al, 1993). To determine whether these terminal sequences represent a genus-specific characteristic, fijiviruses from groups other than group 2 should be analysed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the amino acid sequence identities between the major outer capsid proteins (MOCPs) range from 48 to 56 % (Omura et al, 1989;Xu et al, 1989;Noda et al, 1991 b). In the Fijivirus genus, the nucleotide sequences of MRDV genome segment 6 ($6) (Marzachi et al, 1991) and RBSDV S10 (Uyeda et al, 1990), $8 and $7 (Azuhata et al, 1993) have been reported, but those of their MOCPs are unknown. We previously reported the nucleotide sequence ofNLRV S10 (Noda et al, 1994).…”
mentioning
confidence: 99%